Impact of aromatics and monoterpenes on simulated tropospheric ozone and total OH reactivity. (November 2017) - Porter, William C.; Safieddine, Sarah A.; Heald, Colette L.
Abstract: The accurate representation of volatile organic compounds (VOCs) in models is an important step towards the goal of understanding and predicting many changes in atmospheric constituents relevant to climate change and human health. While isoprene is the most abundant non-methane VOC, many other compounds play a large role in governing pollutant formation and the overall oxidative capacity of the atmosphere. We quantify the impacts of aromatics and monoterpenes, two classes of VOC not included in the standard gas-phase chemistry of the chemical transport model GEOS-Chem, on atmospheric composition. We find that including these compounds increases mean total summer OH reactivity by an average of 11% over the United States, Europe, and Asia. This increased reactivity results in higher simulated levels of O3, raising maximum daily 8-h average O3 in the summer by up to 14 ppb at some NOx -saturated locations. Highlights: Impacts of aromatics and monoterpenes estimated using chemical transport model. Large increases in surface O3 predicted at extremely VOC-sensitive locations. Computational cost could be mitigated through simplified chemistry schemes.